A review paper: critical factors affecting the development of ICT projects in Malaysia - Chew, Chun Meng; Abu Samah, Bahaman; Omar, Siti Zobidah (Canadian Center of Science and Education, 2013)
Malaysia has been stuck at middle-income level since the 1990s. Hence, the government has been aggressively undertaking productivity improvement by enhancing its technological and knowledge capabilities in order to transform the community into a knowledge-based society. However, more than 40% of its population still lives in rural areas and lack basic infrastructure (such as fixed telephone lines or Internet connection). This has led to a wider information gap between the rural and urban communities. The setting up of telecentres is seen as a means by which to bridge this gap, as it will provide public access to ICT services and facilities, particularly in remote areas where such services and facilities are lacking. Malaysia has systematically planned a framework to narrow down the gap; it attempts to offer the best ICT infrastructure to its people, thereby allowing them to adopt ICT as a tool to improve their social-economic status. Although investments and efforts have been in place, however, some of these projects have yet to prove successful, and many projects are still in a developmental stage. In addition, there are few empirical studies on the critical issues surrounding the formation of ICT projects in Malaysia, and we are in dire need of research to fill this gap. This paper provides a discussion of the relevant documents, and a literature analysis, regarding the catalysts and barriers towards the development of ICT projects.